The influence of product quality and brand image on purchasing decisions in tiktok shop within the context of Batam city - Casta Aruan; Alice Erni Husein (International Journal of Applied Finance and Business Studies, 2025)
This study investigates the influence of product quality and brand image on purchase decisions among TikTok Shop consumers in Batam City, Indonesia. Using a quantitative approach and multiple linear regression analysis, data were collected from 100 respondents selected through purposive sampling. The findings reveal that both product quality and brand image have a positive and significant effect on purchase decisions. Specifically, higher perceived product quality, measured through performance, features, reliability, conformity, durability, service capability, aesthetics, and perceived quality, enhances consumer willingness to purchase. Similarly, a strong brand image, comprising company image, user image, and product image, significantly increases consumers’ likelihood of making purchase decisions. These results align with previous research emphasizing that product attributes and brand perception are key determinants of consumer behavior in e-commerce environments. The study provides both theoretical and practical implications, particularly for online sellers and digital marketing strategists seeking to strengthen consumer trust and drive purchase intentions on live-streaming commerce platforms